Thyroid dysfunctions and autoimmunity in breast cancer patients: a prospective case-control study - Chandan Kumar Jha; Anjali Mishra; Subhash B. Yadav; Gaurav Agarwal; Shalini Singh; Gyan Chand; Amit Agarwal; Saroj Kanta Mishra (Archives of Endocrinology and Metabolism, 2020)
ABSTRACT Objective: The relationship of thyroid dysfunction and autoimmunity with breast cancer (BC) continues to be contentious. The primary aim of this study was to estimate the prevalence of thyroid dysfunctions and autoimmunity in BC patients, and the secondary aims were to investigate the relationship of thyroid dysfunction with the clinicopathological profile of and therapy received by BC patients. Materials and methods: This was a single-center prospective case-control study (March 2015-May 2017). Women with BC (n = 191), age-matched healthy controls (n = 166) and malignant controls (patients with cervical cancer, n = 87) were enrolled. Basal serum free thyroxin (fT4), thyrotropin (TSH) and anti-thyroid peroxidase (TPO) antibody levels were measured in all three groups; fT4, TSH and TPO measures were repeated after chemotherapy and at the 1-year follow-up (one year after diagnosis) in the BC patients. Results: The prevalence of overall hypothyroidism and autoimmunity (p = 0.106) did not differ significantly between the three groups, but the rate of clinical hypothyroidism was significantly higher in the BC group than in the healthy control group and the malignant control group (12.2% vs. 3.0% vs. 4.6%, respectively; p = 0.001). BC patients had significantly lower mean basal TSH concentrations than the healthy controls (p = 0.017). The postchemotherapy TSH concentrations were significantly lower (p = 0.001), and the fT4 concentrations were higher, albeit not significantly (p = 1.00), than the respective basal concentrations. The reverse was true for the follow-up values, in which the TSH (p = 1.00) values were higher and the fT4 (p = 0.03) concentrations were lower than the respective basal concentrations. An additional 6% of the BC patients developed clinical hypothyroidism during follow-up. Hypothyroid (p = 0.02) and TPO-positive (p = 0.004) patients had significantly smaller tumors, but their other clinicopathological features were comparable to those without thyroid dysfunction. Conclusions: The prevalence of clinical hypothyroidism requiring thyroxine replacement was significantly high in BC patients and increased further during follow-up. Hence, BC patients should be considered a high-risk group that should receive routine screening for hypothyroidism.